Application of the iymphocyte cytokinesis-block micronucleus assay to populations exposed to petroleum and its derivatives: results from a systematic review and meta-analysis - Angelini, Sabrina; Lorenzo Bermejo, Justo; Ravegnini, Gloria; Sammarini, Giulia; Hrelia, Patrizia (Mutation research. Reviews in mutation research, 2016)
The lymphocyte cytokinesis-block micronucleus (CBMN) assay is applied in many different in vivo biomonitoring studies of human exposure to genotoxic chemicals. Among extensively chemicals investigated, we identified petroleum and its derivatives, in particular benzene and the most common mixture of benzene, toluene, and xylene. Although conflicting results have been reported on the effects of benzene exposure, the number of positive findings in independent studies suggests that occupational exposure to benzene causes DNA damage in peripheral blood lymphocytes. To assess current evidence on this hypothesis, we conducted a meta-analysis. Our aim was to evaluate the effect of benzene exposure on genetic damage, quantified using the CBMN assay on individuals occupationally exposed to petroleum and its derivatives. Statistical analyses were conducted using the rmeta package from the free Software Environment for Statistical Computing R. Combined study results indicated that benzene exposure is associated with an increased level of genetic damage in peripheral blood lymphocytes, as reflected by an increased MN frequency. The summary mean difference in MN frequency between exposed and unexposed individuals was 1.64 (95% CI: 0.80-2.47). Overall, this finding points to MN frequency as a sensitive biomarker which could be used to evaluate genetic damage induced by occupational - industrial or environmental - exposure to benzene. This review also identified some important knowledge gaps as well as the need of large, well-designed studies. In particular, it is fundamental to accurately characterize the investigated population, including dietary habits and genetic variability which could modulate MN frequency in both exposed individuals and unexposed controls. In conclusion, according to present findings the use of the CBMN assay in biomonitoring studies could provide objective evidence to guide prioritization of preventive interventions in subjects occupationally exposed to petroleum derivatives, and in particular benzene.